The three musketeers - Dumas, Alexandre (Leicester : Magna Books, 1994)
When young D'Artagnan initially quarrels with, then befriends, three musketeers and joins them in trying to outwit the enemies of the king and queen.
Keywords: France -- History -- Louis XIII, 1610-1643 -- Fiction; Historical fiction